Detecting muscle contractions using strain gauges. Issue 22 (1st October 2016) - Zizoua, C.; Raison, M.; Boukhenous, S.; Attari, M.; Achiche, S.
Abstract : Myoelectric prostheses aim to help amputees to experience partial function of the absent organ. The sensors usually used to control the prostheses are surface electromyography (sEMG) electrodes, of which the number tends to increase with the increase of the number of degrees of freedom in the recent prostheses, i.e. dozens of sensors today. However, sEMG requires a high sampling frequency, traditionally about 1000 Hz, which drastically limits the number of sensors that the processors can manage. The objective is to develop a device enabling to measure muscle contractions (MCs) with a sampling frequency compared with the movement frequencies. Strain gauges are known for their accuracy, so using them to detect MCs could help to predict the movement intentions of the amputee. The designed devise includes the integration of four strain gauges in silicone rubber that is similar to human skin. The reliability of the sensor results is demonstrated by a comparison with Ag/AgCl electrodes of an electromyography system. The correlation coefficient is very high (0.89) between the tensions measured by the sEMG and the strain gauges. So the advantage of a low sampling frequency compared with sEMG is the potential development of matrices with many strain gauges.